The amino acid homoarginine inhibits atherogenesis by modulating T-cell function - Nitz, K; Lacy, M; Bianchini, M; Wichapong, K; Kücükgöze, IA; Bonfiglio, CA; Migheli, R; Wu, Y; Burger, C; Li, Y; Forné, I; Ammar, C; et al. (American Heart Association, 2022)
Background: Amino acid metabolism is crucial for inflammatory processes during atherogenesis. The endogenous amino acid homoarginine is a robust biomarker for cardiovascular outcome and mortality with high levels being protective. However, the underlying mechanisms remain elusive. We investigated the effect of homoarginine supplementation on atherosclerotic plaque development with a particular focus on inflammation.